EFEKTIFITAS PECS UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANAK TUNARUNGU KELAS VII SMPLB (SINGLE SUBJECT RESEARCH DI SLB YPPLB PADANG) - Rina Trimailani (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract: The background of this study was motivated by the problem that was found in children with hearing impairment grade VII at SMPLB who could not speak a word properly. When communicating, the words that had been spoken were not clear, misspelled and hardly understood by others. This research used experiment approach in single subject research (SSR) form using A-B-A design and data analysis technique that was used was analysis visual graphic. Scoring in this research was done by measure children ability percentage in speaking some available words.Based on the result of the research, at baseline  condition (A1) that had been done five times observation and child only could get 20% score. At intervention condition (B) observation had been done ten times and child’s score increased to 90%.At baseline  condition (A2) observation had done five times and the score increased become 93.33%. From data analysis, it could say that there was improvement from baseline  (A1) to intervention (B) and baseline  (A2). Small data overlap percentage was 40 so that concluded intervention effect by PECS had done well toward speaking skill for deaf child in speaking words. Because of that reason, research hypothesis was accepted. It means that PECS could improve deaf child speaking skill. The researcher suggested to school and teacher to use PECS as teaching media in improving speaking skill of deaf  child    Key word: PECS; Anak Tunarungu; Komunikasi; Kata